Postoperative Study of Bone Gain in Mandibular Alveolar Bone Reconstructed with Screw-Guided Bone Regeneration Technique and Porcine-Derived Xenograft in 42 Edentulous Patient Candidates for Implant-Prosthetic Therapy - Doriana Agop-Forna; Roland Törok; Bianca Törok; Raluca Dragomir; David M. Dohan Ehrenfest; Cristina Dascălu; Carmen Gabriela Stelea (Applied Sciences, 2021)
This study aimed to test whether alveolar bone gain (width and osteodensity) in mandible implant sites, augmented by the screw-guided bone regeneration (S-GBR) technique and the porcine-derived xenograft, differ from that of the mandible sites reconstructed with S-GBR and the bovine-derived xenograft. Materials and method. A total of 42 edentulous patients (mean age 54.60 ± 14.90) were randomly divided into a test group (S-GBR + porcine-derived xenograft) and a control group (S-GBR + bovine-derived xenograft). The immediate implants were placed simultaneously with grafting procedures. The implant site width was measured before teeth extractions and 6 months after the augmentation procedures. Osteodensity bone values were evaluated immediately after the implant placement and at 6 months follow-up. The CBCT sections and Sidexis XG/DVT (Densply/Sirona) software were used to evaluate the changes of the width in the augmented alveolar bone. The NNT Viewer/CT (NewTom) software was used to record the osteodensity changes. Statistical comparisons between the groups were performed by the Mann–Whitney and t-tests (significance level p < 0.05). Results. The mean values of the bone gain at 6 months follow-up (control group vs. test group) were as follows: width (4.107 mm vs. 4.1624 mm); osteodensity (276.83 HU vs. 254.24 HU). The statistical analysis found the absence of statistically significant differences between the two groups regarding the bone gain (width and osteodensity) at 6 months after the augmentation and the immediate implant placement. Conclusions. The horizontal bone and osteodensity gains in the porcine-derived group were similar and without significant statistical differences when compared with the implant sites reconstructed with the bovine-derived xenografts group at 6 months postoperatively. The reconstruction of the mandibular alveolar bone by the S-GBR technique and the porcine-derived xenografts is a valid bone regeneration strategy for edentulous patients with moderate/severe horizontal resorption of the mandibular alveolar bone.